Soil polluted system shapes endophytic fungi communities associated with Arundo donax: a field experiment - Wang, Xiaohui; Wang, Yao; Sun, Yingqiang; Wang, Keyi; Yang, Junbo; Zeng, Danjuan; Mo, Ling; Liao, Jianxiong; Peng, Qianshu; Yao, Yu; Pu, Gaozhong (PeerJ, 2025)
With the expansion of the mining industry, environmental pollution from microelements (MP) and red mud (RM) has become a pressing issue. While bioremediation offers a cost-effective and sustainable solution, plant growth in these polluted environments remains difficult. Arundo donax is one of the few plants capable of surviving in RM-affected soils. To identify endophytic fungi that support A. donax in different contaminated environments and to inform future research combining mycorrhizal techniques with hyperaccumulator plants, we conducted a field experiment. The study compared endophytic fungal communities in A. donax grown in uncontaminated, MP soils contaminated with cadmium (Cd), arsenic (As), and lead (Pb), and RM-contaminated soils. Our findings showed that soil nutrient profiles differed by contamination type, with Cd concentrations in MP soils exceeding national pollution standards (GB 15168-2018) and RM soils characterized by high aluminum (Al), iron (Fe), and alkalinity. There were significant differences in the endophytic fungal community structures across the three soil types (p < 0.001). Co-occurrence network analysis revealed that endophytic fungi in MP soils exhibited competitive niche dynamics, whereas fungi in RM soils tended to share niches. Notably, Pleosporales sp., which accounted for 18% of the relative abundance in RM soils, was identified as a dominant and beneficial endophyte, making it a promising candidate for future bioremediation efforts. This study provides valuable insights into the role of endophytic fungi in phytoremediation and highlights their potential as resources for improving plant-microbe interactions in contaminated environments.
Keywords: Contaminated soil; Red mud soil; Phytoremediation; High throughput sequencing; Microbial network